MODEL CORPORATE SOCIAL RESPONSIBILITY (CSR) BERBASIS AGRIBISNIS PANGAN (STUDI KASUS DI PT. SMART WILAYAH KALIMANTAN TENGAH) - Wilson Daud; Uras Tantulo; Betrixia Barbara (Agrienvi: Jurnal Ilmu Pertanian, 2023)
There is still a conflict of interest in land use, causing land used by farmers for food development to be included as HGU PT. SMART. The research aims to (1) find out the food development practices carried out by PT. SMART, (2) knowing the advantages and weaknesses of food development, (3) knowing the response of stakeholders to food development, (4) analyzing the formulation of CSR models for oil palm plantations based on food agribusiness. The results showed that agribusiness-based PET practices since planning, implementation, and marketing are entirely carried out by farmers. Farmers also individually and in groups conduct monitoring and evaluation, both on farming technicalities, group management, and the implementation of PET as a whole. The advantages and disadvantages of PET are the advantages of implementing PET PT. SMART mainly comes from the direct involvement of farmers in all work and management of farms, weaknesses in the implementation of PET PT. SMART consists of basic work of PET participants, difficulties in procuring saprodi after the crop starts to produce, the inability of farmers because while doing other work, productivity is quite low compared to pilot companies, management of farmer groups, and related government agencies have not been involved sustainably. Stakeholder response to PET practices has generally been good, but it is recognized that increasing the income of PET farmers is not accompanied by the ability of communities to manage their incomes. The formulation of the CSR model of PT. SMART based agribusiness food is (1) CSR of PT. SMART based on food agribusiness uses a model of partnering with other parties, namely partnering with farmers, government and universities, (2) empowering farmers in the CSR model of PT. SMART based on food agribusiness uses a collective farming group approach, while farming uses an integrated farming system.